2011
DOI: 10.1097/ccm.0b013e31820ee1f2
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic hypercapnia enhances the inflammatory response to endotoxin in the lung of spontaneously breathing rats*

Abstract: A 24-hr exposure to therapeutic hypercapnia in endotoxin-stimulated, spontaneously breathing rats is associated with a proinflammatory immune response in the lung and anti-inflammatory response in the spleen as well as an increase in certain histologic indices of endotoxin-induced lung injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The alveolar septal thickness, 3-to 5-mm in 4 and 12 weeks, in the CD-fed rats without LPS was notably lower than that, 10 mm, of the control rats in Norozian et al's study [28]. The higher amount of vitamins E and D 3 for preventing oxidative rancidity of fat in both the CD and HFD than that of typical normal chow may contribute to thinner alveolar septal thickness at baseline in this rats [29].…”
Section: Discussionmentioning
confidence: 87%
“…The alveolar septal thickness, 3-to 5-mm in 4 and 12 weeks, in the CD-fed rats without LPS was notably lower than that, 10 mm, of the control rats in Norozian et al's study [28]. The higher amount of vitamins E and D 3 for preventing oxidative rancidity of fat in both the CD and HFD than that of typical normal chow may contribute to thinner alveolar septal thickness at baseline in this rats [29].…”
Section: Discussionmentioning
confidence: 87%
“…Controversies remain as to the potential mechanisms underlying the effects of hypercapnia on lung neutrophilic infiltration, which depend on the level of PaCO 2 , the duration of hypercapnia, and the route of hypercapnia induction (inhalation or mechanical ventilation). Hypercapnic acidosis has been shown to reduce lung neutrophil infiltration in different ALI models, such as the ischemia-reperfusion model in rabbits (Laffey et al, 2000a), intratracheal instillation (Laffey et al, 2004) and intraperitoneal injection (Norozian et al, 2011) of endotoxin, and cecal ligation and puncture in rats. However, it is not clear whether the protective effects of hypercapnic acidosis in these models are neutrophil-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Acute hypercapnic acidosis has been suggested to attenuate lung injury in ischemic reperfusion (Laffey et al, 2000a), sepsis Higgins et al, 2009), and endotoxin (Norozian et al, 2011) models, raising the possibility of a potential therapeutic application of hypercapnia in acute lung injury (ALI) (therapeutic hypercapnia).…”
Section: Introductionmentioning
confidence: 99%
“…Putative mediators of lung injury shown to be attenuated by therapeutic hypercapnia in these models have included inflammatory cell influx (37,45,72), proinflammatory cytokines (14,38,72), and oxidative stress (31,38,52,72). However, several studies have also indicated the potential for hypercapnia to worsen lung injury (41,53,54) and to potentially cause an increase in inflammation in the noninjured lung (2,45), highlighting the need for further study. Our aim therefore was to examine effects of therapeutic hypercapnia in a new rat model with similarities to human BPD (47), secondary to bleomycin exposure.…”
mentioning
confidence: 99%